2020
DOI: 10.1051/0004-6361/201936090
|View full text |Cite
|
Sign up to set email alerts
|

Active deep learning method for the discovery of objects of interest in large spectroscopic surveys

Abstract: Context. Current archives of the LAMOST telescope contain millions of pipeline-processed spectra that have probably never been seen by human eyes. Most of the rare objects with interesting physical properties, however, can only be identified by visual analysis of their characteristic spectral features. A proper combination of interactive visualisation with modern machine learning techniques opens new ways to discover such objects. Aims. We apply active learning classification methods supported by deep convolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Reviews of anomaly detection methods in time-series data can be found in Goldstein & Uchida (2016) and Blázquez-García et al (2020). Several unsupervised and semisupervised algorithms for astrophysical anomaly detection have been used, including approaches that use Euclidean proximity or clustering information to isolate anomalies (Dutta et al 2007;Henrion et al 2013;Giles & Walkowicz 2019), and approaches that use more complex representations of the data that do not involve their projection into an Euclidean space, such as neural networks, ensemble methods, and active learning (Baron & Poznanski 2017b;Druetto et al 2019;Margalef-Bentabol et al 2020;Škoda, Podsztavek & Tvrdík 2020), as well as Gaussian processes (Chen et al 2018). Significant effort has been put into the problem of anomaly detection in supernova surveys, in particular by the Supernova Anomaly Detection (SNAD) group, which has used isolation forest and active learning to boost the discovery of unusual objects (Pruzhinskaya et al 2019;Aleo et al 2020;Ishida et al 2021).…”
mentioning
confidence: 99%
“…Reviews of anomaly detection methods in time-series data can be found in Goldstein & Uchida (2016) and Blázquez-García et al (2020). Several unsupervised and semisupervised algorithms for astrophysical anomaly detection have been used, including approaches that use Euclidean proximity or clustering information to isolate anomalies (Dutta et al 2007;Henrion et al 2013;Giles & Walkowicz 2019), and approaches that use more complex representations of the data that do not involve their projection into an Euclidean space, such as neural networks, ensemble methods, and active learning (Baron & Poznanski 2017b;Druetto et al 2019;Margalef-Bentabol et al 2020;Škoda, Podsztavek & Tvrdík 2020), as well as Gaussian processes (Chen et al 2018). Significant effort has been put into the problem of anomaly detection in supernova surveys, in particular by the Supernova Anomaly Detection (SNAD) group, which has used isolation forest and active learning to boost the discovery of unusual objects (Pruzhinskaya et al 2019;Aleo et al 2020;Ishida et al 2021).…”
mentioning
confidence: 99%